Hubungan antara Asupan Karbohidrat dan Lemak dengan Kadar Trigliserida pada Pesenam Aerobik Wanita - Diah Nur Khasanah; Idi Setiyobroto; Weni Kurdanti (JURNAL NUTRISIA, 2017)
Background: A long-standing association exists between elevated triglyceride levels and coronary heart disease (CHD). High consumption of fat and carbohydrate influences enhancement of triglycerides level. Sport can reduce cholesterol and triglycerides level. Objective: This research aims to analyze relationship between carbohydrates and fat intakes with triglycerides level on female aerobic gymnasts. Method: This is an observational research using cross sectional research design which was held in Miracle Gymnasium on February17- 18th 2017. 30 subjects were selected as subject because fulfill the requirement (older than 20 years and have willingness to be a subjects). Research variable areintakes of carbohydrate, fat, and triglyceride levels. Result: Result shows 53.3% subjects have high level of carbohydrate and fat intakes followed by 20% subjects with high level of triglycerides. Subjects with high level of carbohydrate, fat intakes and high triglyceride level are 28%. Subjects withsufficient carbohydrate, fat intakes and high triglyceride level are 12.5%.Fisher’s exact test was done to prove hypothesis with results there is no significant relationship between carbohydrate and fat intake with triglyceride level. Conclusions: Subjects with high carbohydrate and fat intake is 53.3% and 20% subjects have high triglyceride level. Relationship between carbohydrate and fat intake with triglyceride level on female aerobic gymnasts is not significant (p>0.05). Keywords: Intake, Carbohydrate, Fat, Aerobic Gymnasts, Triglyceride